Penyuluhan Stunting dan Pemeriksaan Kecacingan di Dusun Paculgowang, Desa Jatirerejo, Kecamatan Diwek, Jombang - Evi Puspita Sari; Anthofani Farhan; Finnalia Restifatul Laily (Yayasan Daarul Huda Kruengmane, 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to the provision of food that does not match nutritional needs. Worms are an infectious disease caused by the worm parasite STH (Soil Transmitted Helminths), the impact of helminthiasis in children is that it causes a decrease in health and nutrition. The purpose of this community service activity is to increase the knowledge of mothers with toddlers about the prevention and treatment of stunting and worm detection. This community service activity is carried out through providing education with counseling and worm screening in toddlers. The target of the activity was residents of Jatirejo village, Diwek sub-district, Jombang. The results of the counseling activities that have been carried out are able to increase the knowledge of mothers with toddlers about the prevention and treatment of stunting. The results of the worm examination showed that 23% of toddlers were positive for helminthiasis.